2013
DOI: 10.1186/1750-1172-8-104
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in the PLEKHG5 gene is relevant with autosomal recessive intermediate Charcot-Marie-Tooth disease

Abstract: BackgroundMutations in the Pleckstrin homology domain-containing, family G member 5 (PLEKHG5) gene has been reported in a family harboring an autosomal recessive lower motor neuron disease (LMND). However, the PLEKHG5 mutation has not been described to cause Charcot-Marie-Tooth disease (CMT).MethodsTo identify the causative mutation in an autosomal recessive intermediate CMT (RI-CMT) family with childhood onset, whole exome sequencing (WES), histopathology, and lower leg MRIs were performed. Expression and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
(27 reference statements)
2
34
0
1
Order By: Relevance
“…There are phosphoinositide-binding domains in several proteins linked to CMT, including dynamin2 (ref. 17), KIF1Bb 18 , neurofilament (NEFL) 19 , Pleckstrin homology (PH) domain containing, family G member 5 (PLEKHG5) 20 and Frabin/ FGD 21,22 . Notably, mutations in the PI(4,5)P 2 -binding domains of dynamin2 (ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are phosphoinositide-binding domains in several proteins linked to CMT, including dynamin2 (ref. 17), KIF1Bb 18 , neurofilament (NEFL) 19 , Pleckstrin homology (PH) domain containing, family G member 5 (PLEKHG5) 20 and Frabin/ FGD 21,22 . Notably, mutations in the PI(4,5)P 2 -binding domains of dynamin2 (ref.…”
mentioning
confidence: 99%
“…17) and PLEKHG5 (ref. 20) have been identified as the causes of CMT. In addition, several different CMT subtypes occur due to mutations in phosphoinositidespecific phosphatases 12 , including MTMR2, MTMR13 and FIG4.…”
mentioning
confidence: 99%
“…A combined axonal and demyelinating phenotype with similar histopathological changes was also found in AD CMT due to GDAP1 mutation [44]. pathogenesis and animal model PLEKHG5 is expressed by both neuronal and glial cells [47,48]. In vitro assays using transfected cells suggested that the missense mutants show impaired ability to activate the NFKB signaling pathway [46,48] and form intracellular aggregates [46].…”
Section: Histopathologymentioning
confidence: 70%
“…pathogenesis and animal model PLEKHG5 is expressed by both neuronal and glial cells [47,48]. In vitro assays using transfected cells suggested that the missense mutants show impaired ability to activate the NFKB signaling pathway [46,48] and form intracellular aggregates [46]. PLEKHG5 knockout mice showed reduced NCVs [47].…”
Section: Histopathologymentioning
confidence: 99%
“…Immunohistochemical studies revealed that the patients expressed a low level of PLEKHG5 in the distal sural nerve and in vitro assays suggested that the PLEKHG5 mutants are defective in activating the NF-κB signaling pathway [79] . Norwegian CMT cases and confirmed that MFN2 gene mutation can also cause intermediate CMT [80] .…”
Section: Plekhg5 and The Ri-cmtc Phenotypementioning
confidence: 99%